Design an Identification Function to Reduce the Computational Resources on the Testing Process of an Analog Electronic Circuit - Temich, Sebastian; Golonek, Tomasz; Grzechca, Damian (Elektronika ir Elektrotechnika, 2019)
In modern electronic circuits, imperfectness in the technological process can cause errors in reaching the correct values of the functional parameters. In order to solve this problem, a novel approach of analog and mixed-signal circuit testing methodology is used. The presented approach allows the testing complexity to be reduced and the testing time to be decreased. For this paper, selected signal features were designated from the transient output signal response. Using regression models with the extracted signal features, the functional parameters of a circuit were determined. An evolutionary determination of the regression models enabled the efficiency of the identification process to be maximized. The proposed methodology is presented for an exemplary CMOS Dickson charge pump circuit.